The Importance of the Islamic Economy and Finance in Combating Poverty and Unemployment - Jaas, Allam (Technium Business and Management, 2022)
This article seeks to examine the role of the Islamic economy and finance in combating the phenomena of poverty and unemployment in Muslim countries. It also proposes mechanisms to address the problem of unemployment through Islamic banks with the aim of achieving economic development and social solidarity, as well as through the alms (Zakat) fund by establishing special funds to finance investment projects needed by the unemployed. Moreover, it studies the crisis of unemployment, as the article shows the role of waqf (which is an Islamic endowment of property to be held in trust and used for a charitable or religious purpose) as an economic institution that can provide jobs for its performers, and provide jobs through projects. The study also shows how the Islamic economy can address the problem of poverty (through zakat and waqf), by giving good loans, to finance small projects, as well as by providing social and economic services to the poor and needy.